ФРАНЦУЗЬКІ ДИПЛОМАТИЧНІ ПРЕДСТАВНИКИ В КРИМУ ТА ЗАПОРОЗЬКО-ТАТАРСЬКІ ВІДНОСИНИ ЧАСІВ НОВОЇ СІЧІ (Zaporizhzhia Historical Review, 2021)
The purpose of the paper is to reveal the general orientation and stages of politics of France concerning Zaporozhzhya and the Zaporozhian – Crimean relations in New Sich Times. The directions and methods of the French consuls’activity in the Crimea and its influence on the essence of Khan’s foreign policy are also elucidated.